2021
DOI: 10.1525/abt.2021.83.7.451
|View full text |Cite
|
Sign up to set email alerts
|

Using Inter-institutional Collaboration to Generate Publishable Findings through Course-Based Undergraduate Research Experiences

Abstract: Course-based undergraduate research experiences (CUREs) are high-impact practices that allow students to conduct research during class time. Benefits of a CURE can be maximized when integrated into a faculty member’s ongoing research. However, this can be particularly challenging for field biologists, especially when field sites are not situated near their university. Indeed, few existing CUREs are field based. One solution is to partner with a collaborator near the field site. We describe a semester-long CURE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…If faculty can initiate CUREs that align with their existing research efforts, it can allow them to benefit from reward structures that encourage research productivity (Smith et al, 2021). There are many Third, we recommend that biology educators work with community engagement experts to build collaborations with community groups working in the local food system.…”
Section: Ne X T S Teps and G Ener Al Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If faculty can initiate CUREs that align with their existing research efforts, it can allow them to benefit from reward structures that encourage research productivity (Smith et al, 2021). There are many Third, we recommend that biology educators work with community engagement experts to build collaborations with community groups working in the local food system.…”
Section: Ne X T S Teps and G Ener Al Discussionmentioning
confidence: 99%
“…A promising approach to engage a large number and more diverse range of students in research is through course‐based undergraduate research experiences (CURE) (Auchincloss et al, 2014; Elgin et al, 2016; Hernandez et al, 2021). If faculty can initiate CUREs that align with their existing research efforts, it can allow them to benefit from reward structures that encourage research productivity (Smith et al, 2021). There are many opportunities for impactful research on applied urban agriculture and urban agroecology that can connect scholars, urban growers, and communities in mutually beneficial partnerships (Nicklay et al, 2020).…”
Section: Next Steps and General Discussionmentioning
confidence: 99%
“…Each funnel trap was fashioned from a clear 2-L plastic bottle and contained a speaker (AGPTEK A02 MP3 player that has an internal speaker) that broadcast stimuli as in Tinghitella et al (2021). This experiment was conducted by students in an animal behavior CURE (Course-based Undergraduate Research Experience) at BYU-Hawaii led by two of the coauthors, SJI and TCS (Smith et al, 2021). In two adjacent fields on campus known to have high cricket and fly abundance, the students deployed funnel traps twice weekly throughout the fall semester (September 24 to November 26, 2019) resulting in 16 replicate trap nights (N = 16 ancestral, 16 white noise, 16 loud purr, and 128 purring exemplars).…”
Section: Field Host Location Experimentsmentioning
confidence: 99%
“…Alternatively, flies may exhibit preferences for certain purring songs. One mechanism that could explain the existence of preferences immediately upon the origin of a new host signal is sensory biases (Ryan et al, 1990 ); flies may prefer songs that have spectral characteristics aligned with their sensory system. For example, O. ochracea ears are tightly tuned to detect songs with a peak frequency around 4.9 kHz (Oshinsky & Hoy, 2002 ; Robert et al, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rodenbusch et al (2016) found students in CUREs were significantly more likely to graduate with STEM degrees within six years and with higher GPAs than similarly prepared students who did not conduct research as freshmen at their institution. CUREs can cost less than full summer research programs, adding to the appeal of utilizing a CURE model to introduce students to authentic research experiences (Ahmad & Al-Thani, 2022; Smith et al, 2021). CUREs reportedly cost approximately $400 per student (Smith et al, 2021), which is low compared to summer research internships where students can be provided with lodging, facilities, and stipends.…”
Section: Introductionmentioning
confidence: 99%